H.E.S.S. observations of the binary system PSR B1259-63/LS 2883 around the 2010/2011 periastron passage - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Aims. We present very high energy (VHE; E > 100 GeV) data from the γ-ray binary system PSR B1259-63/LS 2883 taken around its periastron passage on 15th of December 2010 with the High Energy Stereoscopic System (H.E.S.S.) of Cherenkov Telescopes. We aim to search for a possible TeV counterpart of the GeV flare detected by the Fermi LAT. In addition, we aim to study the current periastron passage in the context of previous observations taken at similar orbital phases, testing the repetitive behaviour of the source. Methods. Observations at VHEs were conducted with H.E.S.S. from 9th to 16th of January 2011. The total dataset amounts to 6 h of observing time. The data taken around the 2004 periastron passage were also re-analysed with the current analysis techniques in order to extend the energy spectrum above 3 TeV to fully compare observation results from 2004 and 2011. Results. The source is detected in the 2011 data at a significance level of 11.5σ revealing an averaged integral flux above 1 TeV of (1.01 ± 0.18 ± 0.20) × 10 cm s. The differential energy spectrum follows a power-law shape with a spectral index Γ = 2.92 ± 0.30 ± 0.20 and a flux normalisation at 1 TeV of N = (1.95 ± 0.32 ± 0.39) × 10 TeV cm s. The measured light curve does not show any evidence for variability of the source on the daily scale. The re-analysis of the 2004 data yields results compatible with the published ones. The differential energy spectrum measured up to 10 TeV is consistent with a power law with a spectral index Γ = 2.81 ± 0.10 ± 0.20 and a flux normalisation at 1 TeV of N = (1.29 ± 0.08 ± 0.26) × 10 TeV cm s. Conclusions. The measured integral flux and the spectral shape of the 2011 data are compatible with the results obtained around previous periastron passages. The absence of variability in the H.E.S.S. data indicates that the GeV flare observed by Fermi LAT in the time period covered also by H.E.S.S. observations originates in a different physical scenario than the TeV emission. Moreover, the comparison of the new results to the results from the 2004 observations made at a similar orbital phase provides a stronger evidence of the repetitive behaviour of the source. © ESO, 2013.
Keywords: Gamma rays: general; Pulsars: individual: PSR B1259-63; Stars: individual: LS 2883; X-rays: binaries